2021
DOI: 10.1038/s41598-021-90840-0
|View full text |Cite
|
Sign up to set email alerts
|

Nitric oxide down-regulates voltage-gated Na+ channel in cardiomyocytes possibly through S-nitrosylation-mediated signaling

Abstract: Nitric oxide (NO) is produced from endothelial cells and cardiomyocytes composing the myocardium and benefits cardiac function through both vascular-dependent and—independent effects. This study was purposed to investigate the possible adverse effect of NO focusing on the voltage-gated Na+ channel in cardiomyocytes. We carried out patch-clamp experiments on rat neonatal cardiomyocytes demonstrating that NOC-18, an NO donor, significantly reduced Na+ channel current in a dose-dependent manner by a long-term app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 50 publications
0
8
0
Order By: Relevance
“…However, a very recent study by Wang and co-workers suggested an indirect mechanism by which S-nitrosylation modulates the cardiac sodium channel expression and function. For instance, NO has been demonstrated to down-regulate SCN5A expression and Na v 1.5 function through S-nitrosylation of regulatory transcription factor FOXO1 [188]. These findings increase our current understanding of the role of redox and free radicals in the regulation of Na v 1.5 function (see [100] for further review).…”
Section: S-nitrosylationmentioning
confidence: 77%
“…However, a very recent study by Wang and co-workers suggested an indirect mechanism by which S-nitrosylation modulates the cardiac sodium channel expression and function. For instance, NO has been demonstrated to down-regulate SCN5A expression and Na v 1.5 function through S-nitrosylation of regulatory transcription factor FOXO1 [188]. These findings increase our current understanding of the role of redox and free radicals in the regulation of Na v 1.5 function (see [100] for further review).…”
Section: S-nitrosylationmentioning
confidence: 77%
“…As a result, myocardial contractility increases. At concentrations, NO causes to produce more amounts of cGMP, by which cardiodepression occurs in response to protein kinase G (PKG) activation with blockade of sarcolemma Ca 2+ channels ( Rastaldo et al, 2007 ; Wang et al, 2021 ). In our study, using L-arginine resulted in increasing NO level so that it exerted a destructive effect and increased arrhythmia in the ketamine/xylazine group.…”
Section: Discussionmentioning
confidence: 99%
“…Images were acquired using a 63× oil objective (Plan-Apochromat 63× [numerical aperture, 1.46] oil immersion objective for differential interference contrast [DIC]; Carl Zeiss, Jena, Germany). All sections were analyzed using a confocal laser microscopy system and software (LSM710, Carl Zeiss, Jena, Germany) that was built around an inverted microscope (Axio Observer Z1, Carl Zeiss, Jena, Germany) as previously described [ 40 ]. The images were saved in TIFF format and analyzed by ImageJ software (Wayne Rasband, National Institutes of Health, Bethesda, MD, USA).…”
Section: Methodsmentioning
confidence: 99%